MORPHOLOGY AND BIOLOGY OF FRESHWATER TANK GOBY, Glossogobius giuris (Hamilton, 1822) FROM INDIAN SUBCONTINENT: A REVIEW - GHOSH, RAJARSHI; GANGULY, SHREYOSREE; BHATTACHARJEE, PRADIP; PAL, ANISH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Glossogobius giuris (Hamilton, 1822), commonly known as tank goby or Bele, is an important food fish of Indian subcontinents for being inexpensive and nutrient-rich. It is widely distributed in freshwater bodies of India, Bangladesh, Pakistan, and Myanmar. The morphological features of this fish are striking with distinct sexual dimorphism. The feeding habits vary with season and different age groups. Based on qualitative and quantitative analysis of gut contents, this fish has been categorized as carnivores. When young ones are abundant, cannibalism has also been observed in this fish group. It has a prolonged breeding period with prolific breeding habits and maximum availability during the rainy season. This fish is full of nutrients with a very low percentage of carbohydrate and lipid but with high protein content and thus increases the demand among fish lovers. The tank goby also drags the attention of aquarium keepers and is considered a small indigenous species in Bangladesh and India. The present review has been prepared to gather the published literature on different biological aspects of Glossogobius giuris, the further study of which will not only help to make fishery industry more vibrant and economically viable but also for conservation of this important food fish.